Duration of Stressed Diphthongs with the Falling and Rising Accent in Present-day Lithuanian Utterances - Anusienė, Lilija (Kalbotyra, 1984)
The purpose of this research was to study the differences of duration between diphthongs with the falling and rising accent in present-day Lithuanian utterances. The results obtained have revealed that:1) diphthongs with the falling accent are longer than diphthongs with the rising accent;2) diphthongs /ai/, /au/ pronounced with the falling and rising accent differ in duration;3) there is almost no difference of duration in the diphthongs /ei/, /uo/, /ie/ pronounced with the falling and rising accent;4) according to their duration diphthongs may be classified into three groups:the longest: au, aimedium: eithe shortest: uo, ie5) duration of the diphthongs /au/, /ai/ is determined by their first component;6) diphthongs with the rising accent in the speech of female subjects show no difference in duration.